Research on Technology of Supporting in Super-Large Section Cut in Working Face with Large Mining Height. (14th October 2021) - Ren, Zhicheng; Zuo, Minghui
Abstract : For the support problem of the super-large section cut in working face with large mining height, the 1105 cut pilot chamber of Zhaogu No. 2 Mine, the roof strata structure detection and the strata movement rule research were conducted. The results prove that concentrate fracture area, gradually sparse fracture area, and rare fracture area regularly distributed from the surface to the deep area of the roof of 1105 cut, and less fracture exists in the rock stratum of roof above 3.5 m, and the stratum of roof within the range of 4–6 m is stable. Authors propose the long bolt and cable combined supporting technology and optimized the design plan applying theoretical calculation and computer numerical simulation. The scheme has been applied in the field of the 1105 super-large section cut in Zhaogu No. 2 Mine. The monitoring results show that the scheme can effectively control surrounding rock of roadway, and the support with long bolt has good effectiveness.